Essential oil composition and antinociceptive activity of Thymus capitatus - Juan Carlos Ramos Gonçalves; Danilo Andrade de Meneses; Aliny Pereira de Vasconcelos; Celyane Alves Piauilino; Fernanda Regina de Castro Almeida; Edoardo Marco Napoli; Giuseppe Ruberto; Demetrius Antônio Machado de Araújo (Taylor & Francis Group, 2017)
Context: The essential oil (EO) from Thymus capitatus Hoff. et Link. (Lamiaceae) has been traditionally used for its medicinal properties, such as anti-inflammatory, analgesic, antioxidant and antimicrobial properties. Objective: Characterize the constituents from T. capitatus EO and further evaluate the antinociceptive activity by in vivo and in vitro procedures. Materials and methods: Gas chromatography-mass spectrometry was used to identify and quantify the constituents of the T. capitatus EO. The antinociceptive activity was evaluated in vivo by the glutamate-induced nociception model in male Swiss mice (25 g), at doses of 3, 6 and 12 mg/kg, 1 h before evaluation of the licking time response (0-15 min). The mechanism of T. capitatus EO (1-500 μg/mL) on the isolated nerve excitability of Wistar rat (300 g) was assessed by the single sucrose technique. Results and discussion: The EO of T. capitatus presented 33 components, mainly monoterpenes and sesquiterpenes, carvacrol (ca. 80%) was its major constituent. T. capitatus EO induced antinociception in orally treated mice (3, 6, and 12 mg/kg) reducing the licking time from control (100.3 ± 11.9 s) to 84.8 ± 12.2, 62.7.6 ± 9.9, and 41.5 ± 12.7 s, respectively (n = 8; p < 0.05). Additionally, we have demonstrated that T. capitatus EO (500 μg/mL) decreased the compound action potential amplitude (VCAP) of about 80.0 ± 4.3% from control recordings (n = 4; p < 0.05). Such activity was presumably mediated through a voltage-gated Na+ channels. Conclusions: The present study demonstrated the antinociceptive activity of Thymus capitatus essential oil, which acts via peripheral nervous excitability blockade.